A graph rewriting system for process platform planning - Zhang, Linda L.; Jiao, Roger J. (Decision Support Systems, 2013)
Facilitating production process planning for product families, process platform planning (P3) has been well recognized as an effective means of achieving production efficiency. To support decision making in P3 automation, this study adopts graph rewriting systems to 1) organize large volumes of product and process data and 2) model production process planning reasoning. The model developed represents the structural and behavioral aspects of process platforms as family graphs and related graph transformations, respectively. In view of its modeling advantage, the system is formally defined using PROGRES. It includes meta, generic, and instance models at three different levels of abstraction. Meta models are defined for family graphs to generalize the patterns common to planning production processes for different product families; generic models are defined to describe entities pertaining to production processes of specific product families; instance models represent production processes producing product variants in a family. The graph rewriting system-based P3 model is applied to textile spindles' production process planning. The results obtained have demonstrated its potential and feasibility to support decision making in P3 automation. ► We highlight the importance of process platform planning for achieving product family production efficiency. ► Process platform planning is presented in detail in terms of both static structure and dynamic behavior. ► A graph rewriting system-based process platform planning model is developed. ► We report textile spindle production to demonstrate the process platform planning model developed.